The use of participatory method in learning of short story writing based on personal experience at SMKN 1 Labang - Ardiyansah (Penerbit STKIP PGRI Bangkalan, 2019)
The purpose of this study is to describe the activities of teachers in learning to write personal experiences using participatory methods. This research takes the form of descriptive qualitative on class action supported by quantitative data. The research instrument used in the form of observation checklist on the activities of teachers and students, and tests of learning outcomes. The results of student learning at the first meeting on cycle 1 were still below the achievement of student pension criteria with a 19% completeness . Meanwhile in the second meeting on cycle 2, it can be seen in the achievement of the average learning outcomes of 66.66 with 33% completeness of learning outcomes so that it can be concluded the learning outcomes of writing short stories based on personal experience using participatory methods are quite effective .